Preserving Local Wisdom: A Semiotic Analysis of Lahat's Regional Songs for Character Education - Effendi, Darwin; Wahidy, Achmad; Riyanto (Journal for Lesson and Learning Studies, 2024)
The lack of attention to preserving regional songs as a medium of learning based on local wisdom poses challenges in cultural preservation and character education. This study aims to analyze the regional songs of Lahat as representations of local wisdom using Roland Barthes' semiotic approach. The data were analyzed by identifying elements such as lyrics, melody, and musical instruments to uncover the denotative, connotative, and mythological meanings embedded in these songs. The findings reveal that Lahat's regional songs carry profound symbolic meanings, reflecting the social, cultural, and religious values of the local community. The lyrics serve as a medium for conveying moral messages, the melodies provide aesthetic value, while the musical instruments enrich the transmission of traditional knowledge. These findings underscore that Lahat’s regional songs are not merely artistic creations but also valuable cultural heritage with significant potential to support character education. The study concludes by emphasizing the importance of preserving and promoting regional songs as a medium of learning based on local wisdom. This can be achieved by integrating these songs into educational practices to instill cultural and moral values in the younger generation while ensuring the continuity of local traditions.